Commodification Of Mak Yong Mask Performance As A Cultural Tourism Attraction In Mantang Island - Arbi Ntan Era Komala (Jurnal Pendidikan Tari, 2021)
This article aims to describe and reveal the commodification of Mak Yong Mask Performing Arts as a tourist attraction on Mantang Island. Mak Yong mask is a traditional performing art of the Malay community which is created from a combination of elements of ritual, performing arts, dance, music and singing. This performance has been recognized by UNESCO (United Nations Educational, Scientific and Cultural Organization) as an intangible cultural heritage belonging to three allied countries, namely Malaysia, Thailand, and Indonesia. Mak Yong’s mask on Mantang Island has a characteristic that is the use of masks as property. Qualitative research methods are carried out using interview, observation, and literature studies. An ethnographic approach with commodification theory is used to observe changes in the performing arts as a form of community negotiation on cultural values. The results of the discussion in this study indicate the commodification of form, time, stage, and desacralization. Changes in the performing arts of Mak Yong masks are influenced by tourism packaging factors without losing the value of the meaning and function of this art as community identity. This effort is carried out as a form of artistic response to the function of performing arts as a cultural tourism.